If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -5x) + 2(5x + 2) = 3 + -1x (4 * 3 + -5x * 3) + 2(5x + 2) = 3 + -1x (12 + -15x) + 2(5x + 2) = 3 + -1x Reorder the terms: 12 + -15x + 2(2 + 5x) = 3 + -1x 12 + -15x + (2 * 2 + 5x * 2) = 3 + -1x 12 + -15x + (4 + 10x) = 3 + -1x Reorder the terms: 12 + 4 + -15x + 10x = 3 + -1x Combine like terms: 12 + 4 = 16 16 + -15x + 10x = 3 + -1x Combine like terms: -15x + 10x = -5x 16 + -5x = 3 + -1x Solving 16 + -5x = 3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 16 + -5x + x = 3 + -1x + x Combine like terms: -5x + x = -4x 16 + -4x = 3 + -1x + x Combine like terms: -1x + x = 0 16 + -4x = 3 + 0 16 + -4x = 3 Add '-16' to each side of the equation. 16 + -16 + -4x = 3 + -16 Combine like terms: 16 + -16 = 0 0 + -4x = 3 + -16 -4x = 3 + -16 Combine like terms: 3 + -16 = -13 -4x = -13 Divide each side by '-4'. x = 3.25 Simplifying x = 3.25
| 4x+36=7x-84 | | 11x+2=3x+66 | | 8-4m=20 | | 7-3z=19 | | 5(3m-2)+3m= | | 3(n-2)=18 | | 8x+16+4x=4 | | 3k+5=2K+19 | | 3(n-2)=13 | | 15-8x=-1-10x | | 2a-6=8 | | 7x-5=50-4x | | 7n-6+2n=2(4n-3) | | 144.9/150.7= | | 3.5=4-3*x | | 150.7/144.9= | | m^3-3m^2-m+4=0 | | -[7z-(16z+9)]=9+(8z+3) | | -x^2+10x+30000=0 | | 7n-11= | | n+19*19=576 | | 4x+5(x-10)=4(x-10) | | x^2-4x-18=0 | | 3x+4(x-8)-x=1(10x+15) | | 12m^2-10m-2=0 | | 2x-4(3x+9)=7-2(3-6x) | | (n-4)*5=15 | | 3z-9=(5z-1) | | 148-7x=38x+23 | | x+4=-2x-8 | | 5x-9x+4=-2x+6 | | 11+2m=3m+7 |